Пошук архітектурних концепцій розвитку міста Прилуки як складова навчального процесу на кафедрі дизайну архітектурного середовища Національного університету “Львівська політехніка” - Богданова, Юлія; Копиляк, Ігор; Bohdanova, Yuliia; Kopylyak, Ihor (Видавництво Львівської політехніки, 2022)
У статті показано місце конкурсного проєктування в навчальному процесі кафедри дизайну архітектурного середовища. Роботи студентів виконувалися за реальними завданнями, представленими адміністрацією міста Прилуки на Чернігівщині. Ці проєкти були цікавими з огляду на те, що здійснювали дуже різні завдання, пов’язані з дизайном архітектурного середовища в місті: від великих концептуальних рішень до вузьких і прагматичних тем, що дозволило відійти від абстрактних універсальних вправ, які здавна опрацьовуються академічною школою. Півріччя, яке було присвячене пошуку нових концепцій розвитку архітектурного середовища міста Прилуки, висвітлило відмінності між навчальним та реальним проєктуванням та дозволило безпосередньо наблизити студентів до виконання завдань, які очікують їх у подальшому професійному житті.

For almost twenty years of existence of the Department of Architectural Environment Design, a wide range of areas of its activity has been formed. Each of them is headed by teachers-specialists who are employees of the department, and both narrowly directed individual project proposals and sections of largescale work are decided. Also, over the past ten years, fifth-year students have been working in the field of competitive design. Quite often, these were topics announced in the direction of international cooperation of the department. However, due to changes in the world associated with the coronavirus epidemic in 2019, the Department of Architectural Environment Design was forced to stop such activities. Another reason for the search for new design vectors was the desire to revive the activities of the research laboratory that operated in the department. Futuristic projects developed by the department partially got on the internet, where they were viewed by a large number of people. So, at the beginning of 2021, an active public figure of the Pryluky city applied to the Department of Architectural Environment Design. The essence of his request was that despite the high-quality landscaping works carried out, in general, the city does not have a look suitable for the XXI century. Several topical areas were chosen for the work: colouristic design of facades of multiapartment residential buildings of the 1950-60s; the concept of development of the “Hydropark”; the architectural and spatial concept of the “Heroes' Memorial” and Taras Shevchenko square. During the spring semester, teachers and students developed more than sixteen projects that could become the foundation for their implementation by the city's community in the future. The implementation of such a design is extremely useful for higher education. After all, students even in the process of studying begin to understand that the tasks that an architect can perform are extremely diverse: from the general plans of cities to the colour scheme of facades, or the development of individual furniture design. It is also important to teach students to work in teams and listen to the requirements of customers.
Search for architectural concepts of Priluky development as a component of the educational process at the department of architectural environment design in the Lviv Polytechnic National University
Keywords: конкурсне проєктування; навчальні проєкти; реальне проєктування; концепції розвитку; архітектурне середовище міста; Прилуки; competitive design; educational projects; real design; development concepts; architectural environment of the city; Pryluky; 721